A functional corona around extracellular vesicles enhances angiogenesis, skin regeneration and immunomodulation. Issue 4 (9th April 2022) - Wolf, Martin; Poupardin, Rodolphe W.; Ebner‐Peking, Patricia; Andrade, André Cronemberger; Blöchl, Constantin; Obermayer, Astrid; Gomes, Fausto Gueths; Vari, Balazs; Maeding, Nicole; Eminger, Essi; Binder, Heide‐Marie; Raninger, Anna M.; et al.
Abstract: Nanoparticles can acquire a plasma protein corona defining their biological identity. Corona functions were previously considered for cell‐derived extracellular vesicles (EVs). Here we demonstrate that nano‐sized EVs from therapy‐grade human placental‐expanded (PLX) stromal cells are surrounded by an imageable and functional protein corona when enriched with permissive technology. Scalable EV separation from cell‐secreted soluble factors via tangential flow‐filtration (TFF) and subtractive tandem mass‐tag (TMT) proteomics revealed significant enrichment of predominantly immunomodulatory and proangiogenic proteins. Western blot, calcein‐based flow cytometry, super‐resolution and electron microscopy verified EV identity. PLX‐EVs partly protected corona proteins from protease digestion. EVs significantly ameliorated human skin regeneration and angiogenesis in vivo, induced differential signalling in immune cells, and dose‐dependently inhibited T cell proliferation in vitro. Corona removal by size‐exclusion or ultracentrifugation abrogated angiogenesis. Re‐establishing an artificial corona by cloaking EVs with fluorescent albumin as a model protein or defined proangiogenic factors was depicted by super‐resolution microscopy, electron microscopy and zeta‐potential shift, and served as a proof‐of‐concept. Understanding EV corona formation will improve rational EV‐inspired nano‐therapy design.